Workers’ Characteristics of Hearing Loss at Soekarno-Hatta International Airport, Indonesia - Timanta, Andrew Ebeneizer; Haryanto, Budi; Wulandari, Ririn Arminsih (UI Scholars Hub, 2023)
This study aimed to analyze the characteristics and factors of worker behavior, including age, the use of ear protection, work duration, a record of diabetes mellitus or hypertension, work rotation, and noise hazards involved in hearing loss in PT. X at Soekarno-Hatta International Airport, Indonesia. A cross-sectional study from May 2017 to June 2017 involved 73 workers in the power service area (TZ Unit) exposed to noise levels ≥85 dBA, using an audiometry test for hearing loss and Sound Level Meter for noise hazards was conducted. The Chi-square test showed a significant correlation between age (OR 8.4, 95% Cl = 1.6-44.1), work duration (OR 7.6, 95% Cl = 0.9-67.2), and the use of ear protection (OR 7.8, 95% Cl = 1.4-44.2) with hearing loss in workers in the power service area. The multivariate analysis revealed that workers exposed to a noise level of 85 dBA had a 1.7 times greater risk of hearing loss than workers exposed to a noise level of age, work duration, use of ear protection, medical history, and work rotation.